Analisis Tarif Angkutan Umum Berdasarkan Biaya Operasional Kendaraan (Studi kasus Bus Trans Lampung Trayek Bandar Lampung – Bandara Raden Inten II) - Kusuma, Ivonne Nisrina; Sulistyorini, Rahayu; Putra, Sasana (Universitas Lampung, 2019)
Determination of tariff rates must be able to bridge the interests of passengers and operators of public transport. The Trans Lampung Bus services for people in various travel routes, one of them is from Bandar Lampung - Raden Inten Airport and vice versa. Data is obtained by carrying out load factor surveys on Trans Lampung Bus Route Bandar Lampung - Raden Inten II Airport and conducting interviews with PT. Trans Lampung. Then the data is analyzed, the results of data analysis to determine the amount of Vehicle Operating Costs (BOK).According by BOK based tariffs with the results of a survey conducted by researchers were able to obtain 11,43% of existing load factor and a tariff of Rp38.100,00/passenger. Based on the data obtained from the Trans Lampung bus on (weekday) 5th, 12th, 19th and 26th of November 2018 and on (weekend) 4th, 11th, 18th and 25th of November 2018 with a load factor of 12,58% to obtain BOK tariff is Rp34.700,00/passenger. Based on data obtained from the Trans Lampung bus on Monday (weekday), Sunday (weekend), the average load factor in one year (January - December 2018) is 14,46%, so the BOK tariff is Rp30.000,00/passenger. Based on the survey results of load factor sister Cahya Ayu Afrisca on 10 September – 3 November 2018 the load factor was obtained on Monday (weekday) and Sunday (weekend) was 21,79% so that the BOK tariff is Rp20.100,00/passenger.Keywords: tariffs, public transportation, Vehicle Operating Costs, BOK.